Current treatment options for cluster headache: limitations and the unmet need for better and specific treatments—a consensus article - Nunu Laura Timotheussen Lund; Anja Sofie Petersen; Rolf Fronczek; Jacob Tfelt-Hansen; Andrea Carmine Belin; Tore Meisingset; Erling Tronvik; Anna Steinberg; Charly Gaul; Rigmor Højland Jensen (The Journal of Headache and Pain, 2023)
Abstract Aim Treatment for cluster headache is currently based on a trial-and-error approach. The available preventive treatment is unspecific and based on few and small studies not adhering to modern standards. Therefore, the authors collaborated to discuss acute and preventive treatment in cluster headache, addressing the unmet need of safe and tolerable preventive medication from the perspectives of people with cluster headache and society, headache specialist and cardiologist. Findings The impact of cluster headache on personal life is substantial. Mean annual direct and indirect costs of cluster headache are more than 11,000 Euros per patient. For acute treatment, the main problems are treatment response, availability, costs and, for triptans, contraindications and the maximum use allowed. Intermediate treatment with steroids and greater occipital nerve blocks are effective but cannot be used continuously. Preventive treatment is sparsely studied and overall limited by relatively low efficacy and side effects. Neurostimulation is a relevant option for treatment-refractory chronic patients. From a cardiologist’s perspective use of verapamil and triptans may be worrisome and regular follow-up is essential when using verapamil and lithium. Conclusion We find that there is a great and unmet need to pursue novel and targeted preventive modalities to suppress the horrific pain attacks for people with cluster headache. Graphical Abstract